Einer aus den hohen Artikeln des Allerheiligesten bepstlichen glaubens genant Donatio Constantini Durch D. Marti. Luther Verdeudscht inn das auffgeschobene Concilium von Mantua. - Luther, Martin, 1483-1546; Valla, Lorenzo, 1407-1457; Lufft, Hans, 1495-1584? (Wittemberg : [Hans Lufft], 1537)
Luther's translation of the Latin Constitutum Constantini followed by his notes and comments.
Decorated title page.
Some annotations in pencil in a modern hand, including on title page.
Colophon: Bedrückt zu Witemberg durch Hans Lufft. M.D.XXXVII. Lufft is not mentioned on the title page.
Printer's devise.
Gothic type.
Woodcut initials.